2019
DOI: 10.1080/21665095.2019.1678186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adaptation practices on crop productivity in northwest Ethiopia: an endogenous switching estimation

Abstract: Climate change and variability adversely affect smallholder farmers in developing countries, including Ethiopia. In response, farmers are adopting various adaptation strategies. However, there is a paucity of studies examining whether or not these responses benefit farmers in increasing crop productivity. Cognizant of this fact and its policy importance, this study empirically analyzes the impact of adaptation strategies on crop productivity in northwest Ethiopia. We collected data through household survey que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 42 publications
4
20
1
1
Order By: Relevance
“…The endogenous switching regression model (ESRM) accounts for observed and unobserved bias by estimating a simultaneous equation model (Lokshin & Sajaia, 2004). The ETRM is nested in ESRM and is widely applied in the analysis of the welfare impact of policies and technology adoption (Adebayo, Bolarin, Oyewale, & Kehinde, 2018; Adego, Simane, & Woldie, 2019; Adela & Aurbacher, 2018; Heckman, Tobias, & Vytlacil, 2003; Mekonnen, 2017). Other relevant studies have applied ESRM to analyse the effect of land‐use changes on water quality (Abildtrup, Garcia, & Kere, 2015), the effect of a large dam on agricultural production (Chen, Hsu, & Wang, 2018), the effect of climate exposure on afforestation (Oyekale & Oyekale, 2019), and the effect of forced displacement on income (Do Yun & Waldorf, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The endogenous switching regression model (ESRM) accounts for observed and unobserved bias by estimating a simultaneous equation model (Lokshin & Sajaia, 2004). The ETRM is nested in ESRM and is widely applied in the analysis of the welfare impact of policies and technology adoption (Adebayo, Bolarin, Oyewale, & Kehinde, 2018; Adego, Simane, & Woldie, 2019; Adela & Aurbacher, 2018; Heckman, Tobias, & Vytlacil, 2003; Mekonnen, 2017). Other relevant studies have applied ESRM to analyse the effect of land‐use changes on water quality (Abildtrup, Garcia, & Kere, 2015), the effect of a large dam on agricultural production (Chen, Hsu, & Wang, 2018), the effect of climate exposure on afforestation (Oyekale & Oyekale, 2019), and the effect of forced displacement on income (Do Yun & Waldorf, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, specific experiences have shown that adopting basic management practices may bring remarkable economic gains to family farmers facing yield-limiting factors (Adego et al, 2019;Onyeneke, 2020;Shahzad & Abdulai, 2020). In this context, climate resilience programmes have been formulated to help counteract the effects of climate change on vulnerable rural areas in the developing world.…”
Section: Introductionmentioning
confidence: 99%
“…As study with [4] agricultural productivity remain stagnant in sub-Saharan Africa. Additionally, smallholder farmers in developing countries are affected by climate change and variability adversely [5]. As a result, farmers are taking up various altered copy strategies to reduce the vulnerability of farming output.…”
Section: Introductionmentioning
confidence: 99%